FARMER'S PROFITABILITY OF POTATO CULTIVATION AT RANGPUR DISTRICT: THE SOCIO-ECONOMIC CONTEXT OF BANGLADESH - Abu Zafar Ahmed Mukul; Shah Johir Rayhan; Masudul Hassan (Russian Journal of Agricultural and Socio-Economic Sciences, 2013)
Bangladesh is predominantly an agricultural country. Agriculture is the indispensable culture of Bangladesh. Agriculture has a enceinte contribution to the Gross Domestic Product (GDP) of the country. Earlier more than 50% of GDP came from this sector. Various types of crops are produced in this country. These crops might have been categorized into two-food crops and cash crops. Potato is one of the food-stuff of the most people of the world as well as Bangladesh. Potato crop is being treated as foremost crop. This study was conducted to approximation the cost of production and profitability of potato producers at Rangpur district. Data collected from 30 farmers using simple random sampling technique. The potato farmers showed individual differences in their socio-economic characteristics and absolute majority of them belonged to young age category (20-35 years) having medium family size, illiterate, medium farm size (0.34-1.0 acre), (1-10 years) farming experience. Most of the respondents used cardinal variety of potato seed and sell their output at home. Farmers who sell potato in the market were more profitable than others. The study also designates that the large farmers were most profitable compared to others. Major problem faced by the potato farmers were lower price of potato during harvesting period, price fluctuation , shortage of capital, high charge of cold storage, lack of good quality seed, perish ability of potato, poor storage facility, higher price of inputs and lack of marketing facility etc. Proper steps should be postulated by Government to puzzle out this problem. The determinations of the study will generate basic economic data on the production practices of potato. At long last it will be helpful to the planners and policy makers in contriving micro or macro level policy for the enlargement of potato production in the country.